External influences on and conditions for community logging management in Cameroon - Blas, D.E. de; Pérez, M.R.; Sayer, Jeffrey A.; Lescuyer, G.; Nasi, Robert; Karsenty, A. (2009)
Community-based forest management has been promoted widely to enable local communities capture the value of the forests they inhabit. Most community forests have focused on non-timber forest products. In Cameroon, the 1994 Forest Law introduced community forestry with a strong emphasis on timber harvesting. We analyze a stratified sample of 20 community forests to assess the conditions that may enable communities to capture value from their forests and the effects of the external support they have received. While communities seem to be benefiting financially from the forest, their capacity to do so is limited by their inability to capture value added in the market chain. This is due to a lack of technical skills, excessive distance to markets, competition from industrial loggers who access the newly opened logging areas, and the intensity of external help they receive. The result is a sub-optimal contribution of community forests to local development.